Is green tea still 'green'?. Issue 2 (30th August 2016) - Li, Yong; Zheng, Xunhua; Fu, Xiaoqing; Wu, Yanzheng
Abstract : The contemporary tea industry in China is associated with high tea production and high nitrous oxide (N2 O) emissions, due to the application of large quantities of nitrogen (N) fertilisers, and the intrinsic characteristics of tea field soils. In total, the Chinese tea plantations may have emitted 40.9 Gg N year –1 of N2 O for 2013, accounting for 85% of emissions from global tea plantations. Such emissions are significant, unneglectable and need to be incorporated into the national greenhouse gas inventory. The current average N2 O emission rate and emission intensity of tea plantations in China are as high as 16.6 kg N2 O‐N ha –1 year –1 and 21.3 g N2 O‐N per kg tea production (several times greater than in other croplands), respectively, severely damaging the 'green' signature of Chinese green teas. To reduce the risk of a sudden collapse of the currently booming tea industry, due to the dramatic decline of economic profit in the event of an agricultural carbon tax scheme being implemented in the near future, investigations of the mechanisms for the high rate of N2 O emissions and the effective N2 O mitigation practices in tea plantations are urgently needed. Of the counties with large tea plantations, only China, India and Japan have contributed data. The measurement and research of N2 O emissions from other large tea plantations in Africa, South and Central Asia should be alerted by this report to close the global gap of N2 O emissions from tea plantations. Abstract : This paper raised an issue on the significant contribution of Chinese contemporary tea industry to greenhouse gas emissions, which has not yet been incorporated into the current national greenhouse gas inventory. It reported that the average nitrous oxide emission rate and emission intensity of tea plantations in China are as high as 16.6 kg N ha ‐1 yr ‐1 and 21.3 g N per kg tea production, respectively, suggesting that the current Chinese tea industry is not on the right track for "green" or sustainable development, and therefore steps need to be taken to decrease its nitrous oxide emissions. e00021